Pengembangan Media Pembelajaran Berbasis E-Learning di SMK Negeri 1 Bojonegoro - Wulansari, Sih; Suhartini, Ratna (Jurnal Pendidikan Madrasah, 2024)
The development of e-learning-based learning media is an innovation in the world of education that aims to increase the effectiveness and efficiency of the teaching and learning process. This research aims to develop learning media that are interactive, easily accessible, and in accordance with the needs of students in the digital era. The results showed that the implementation of this media in the classroom showed a significant improvement in student learning outcomes and their active participation during learning. Additionally, features such as interactive videos, online quizzes, and discussion forums help create an engaging and collaborative learning experience. E-learning-based learning media not only supports distance learning but also enriches face-to-face learning by providing flexible and technology-based resources. Further development recommendations include integration with artificial intelligence (AI) and personalization of learning content to meet the individual needs of students.